Dry Needling Produces Mild Injuries Irrespective to Muscle Stiffness and Tension in Ex Vivo Mice Muscles - Marc Bosque; Ramon Margalef; Oscar Carvajal; David Álvarez; Manel M. Santafe (Pain Research and Management)
Numerous studies have suggested that the myofascial trigger points are responsible for most of the myofascial pain syndrome, so it seems reasonable that its destruction is a good therapeutic solution. The effectiveness of dry needling (DN) has been confirmed in muscles with myofascial trigger points, hypertonicity, and spasticity. The objective of this study is to analyze the need of repetitive punctures on muscles in different situations. The levator auris longus (LAL) muscle and gastrocnemius muscle from adult male Swiss mice were dissected and maintained alive, while being submerged in an oxygenated Ringer’s solution. DN was evaluated under four animal models, mimicking the human condition: normal healthy muscles, muscle fibers with contraction knots, muscles submerged in a depolarizing Ringer solution (KCl-CaCl2), and muscles submerged in Ringer solution with formalin. Thereafter, samples were evaluated with optical microscopy (LAL) and scanning electron microscopy (gastrocnemius). Healthy muscles allowed the penetration of needles between fibers with minimal injuries. In muscles with contraction knots, the needle separated many muscle fibers, and several others were injured, while blood vessels and intramuscular nerves were mostly not injured. Muscles submerged in a depolarizing solution inducing sustained contraction showed more injured muscular fibers and several muscle fibers separated by the needle. Finally, the muscles submerged in Ringer solution with formalin showed a few number of injured muscular fibers and abundant muscle fibers separated by the needle. Scanning electron microscopy images confirm the optical analyses. In summary, dry needling is a technique that causes mild injury irrespective of the muscle tone.